2018
DOI: 10.1002/jcb.26541
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of oral cancer cells to 5‐ALA‐mediated photodynamic therapy

Abstract: Photodynamic therapy (PDT) has been indicated for oral squamous cell carcinoma (OSCC) at early stages. Chemo and radio-resistance are frequently observed in OSCC, but it is unknown whether this tumor can develop resistance to PDT. It was investigated the process of acquiring resistance to multiple cycles of PDT by using OSCC cells. We also analyzed the expression of anti-apoptotic proteins and those related to Akt/mTOR pathway. Sub-lethal doses of PDT were applied, consisting of a constant concentration of 5-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 41 publications
0
23
0
5
Order By: Relevance
“…In this case, the viral load fluctuated at high levels during 6 successive cycles of ALA-PDT, indicating that the patient responded poorly to ALA-PDT. It is reported that oral squamous cell carcinoma (OSCC) cells acquired resistance to multiple cycles of ALA-PDT by reducing PpIX synthesis and activating signaling pathways related to the inhibition of apoptosis and improvement of cell proliferation (Rosin et al, 2018). In addition, different subgroups of breast cancers showed different sensitivity to hypericin-PDT (Theodossiou et al, 2017).…”
Section: Dear Editormentioning
confidence: 99%
“…In this case, the viral load fluctuated at high levels during 6 successive cycles of ALA-PDT, indicating that the patient responded poorly to ALA-PDT. It is reported that oral squamous cell carcinoma (OSCC) cells acquired resistance to multiple cycles of ALA-PDT by reducing PpIX synthesis and activating signaling pathways related to the inhibition of apoptosis and improvement of cell proliferation (Rosin et al, 2018). In addition, different subgroups of breast cancers showed different sensitivity to hypericin-PDT (Theodossiou et al, 2017).…”
Section: Dear Editormentioning
confidence: 99%
“…De fato, no presente trabalho demonstramos que essas células desenvolveram resistência à PDT, porém esta foi com uma taxa menor se comparada à constatada em estudo anterior envolvendo células de carcinoma epidermóide oral (CEO) (linhagem SCC9) (Rosin et al, 2017), sendo que ambas as linhagens foram expostas à mesma dose de luz inicial. Detectamos também que as células displásicas eram mais sensíveis ao tratamento do que as células neoplásicas, demonstrando taxa de viabilidade menor a cada ciclo de PDT instituído, se comparadas às detectadas para as células de CEO.…”
Section: Discussionunclassified
“…Um fato interessante foi termos verificado que as células sobreviventes no grupo PDT geração 1, tanto na linhagem SCC9 quanto na DOK expostas a um ciclo de PDT, exibiram maior invasão, ao contrário daquelas da geração 4. No estudo anterior já tínhamos detectado que a PDT geração 1 de células SCC9 exibia alto potencial de migração (Rosin et al, 2017). Outros trabalhos também evidenciaram um fenótipo mais invasivo de células sobreviventes à PDT mediada pelo 5-ALA, o qual tem sido associado a maior produção de iNOS pelas células sobreviventes a um ciclo de PDT (Bhowmick;Girotti, 2014;Fahey;Girotti, 2015).…”
Section: Discussionunclassified
See 2 more Smart Citations